2019
DOI: 10.21203/rs.2.12984/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic value of TP53 concurrent mutations for EGFR- TKIs and ALK-TKIs based targeted therapy in advanced non-small cell lung cancer: a meta-analysis

Abstract: Background The prognostic significance of TP53 concurrent mutations in patients with epidermal growth factor receptor (EGFR)- or anaplastic lymphoma kinase (ALK)- mutated advanced non–small-cell lung cancer (NSCLC) who received EGFR-tyrosine kinase inhibitors (TKIs) or ALK-TKIs based targeted therapy remains controversial. Therefore, the present meta-analysis was performed to investigate the association between TP53 concurrent mutations and prognosis of patients with advanced NSCLC undergoing EGFR-TKIs or ALK… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…Given the above analyses of prognostic characteristics of multiple genes in lung cancer, we conclude that the EGFR + TP53 mutation subtype indicates a poorer prognosis than the EGFR mutation and multiple gene mutation subtypes, but there is no significant prognosis difference between the EGFR mutation and multiple gene mutation subtypes. This observation is in line with recent clinical outcome studies on non-small cell lung cancer with concurrent EGFR and TP53 mutations ( Hou et al., 2019 ; Jiao et al., 2018 ; Qin et al., 2020 ).
Figure 4 Expression of differentially expressed prognostic genes and pairwise comparison among subtypes Unfavorable and favorable prognostic genes are shown in the left and right panels, respectively.
…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Given the above analyses of prognostic characteristics of multiple genes in lung cancer, we conclude that the EGFR + TP53 mutation subtype indicates a poorer prognosis than the EGFR mutation and multiple gene mutation subtypes, but there is no significant prognosis difference between the EGFR mutation and multiple gene mutation subtypes. This observation is in line with recent clinical outcome studies on non-small cell lung cancer with concurrent EGFR and TP53 mutations ( Hou et al., 2019 ; Jiao et al., 2018 ; Qin et al., 2020 ).
Figure 4 Expression of differentially expressed prognostic genes and pairwise comparison among subtypes Unfavorable and favorable prognostic genes are shown in the left and right panels, respectively.
…”
Section: Resultssupporting
confidence: 89%
“…Integrating multiple known lung-cancer-related prognostic gene expressions to infer the prognosis, we showed that the EGFR + TP53 mutation subtype has poorer prognosis than other subtypes, which is consistent with studies showing that patients harboring the EGFR and TP53 co-mutation have worse prognosis than patients harboring EGFR mutation only ( Hou et al., 2019 ; Jiao et al., 2018 ; Qin et al., 2020 ). Notably, our approach for the analysis is quite different from studies that mainly adopt survival analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Concurrent TP53 mutation is now considered a negative prognostic factor in patients with EGFR-mutated LUAD that receive EGFR-TKIs. 53 A Chinese report found that concurrent TP53 mutation was more prevalent among young patients. 15 Gene fusions such as ALK, ROS, and RET rearrangements, though uncommon, are among the most frequent gene alterations that can be targeted in lung cancer.…”
Section: Genomic Profiling In Aya With Lung Cancermentioning
confidence: 99%
“…H2228 cells carry a TP53 mutation and a NFE2L2 (Nrf2) G31A gain-of-function mutation, which constitutively activates the Nrf2 signaling pathway. Both mutations are associated with low sensitivity to ALKi 7, 8, 21 . To confirm the dysregulation of the Nrf2 signaling pathway, we compared the expression of Nrf2 and its target genes at both the mRNA and protein level in H3122 and H2228 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms for intrinsic resistance are poorly understood, but have been proposed to relate to e.g. the precise ALK fusion variant 5 , or TP53 mutations which frequently co-occur with ALK rearrangements 6,7,8 . Among tumors that acquire resistance to crizotinib, about 30% exhibit ALK-dependent resistance mechanisms, particularly ALK mutations and/or amplification 9,10 .…”
Section: Introductionmentioning
confidence: 99%